2020
DOI: 10.1002/adfm.202000378
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Polydopamine Films with Phospholipid Nanodiscs Containing a Glycophorin A Domain

Abstract: Cellular membranes have long served as an inspiration for nanomaterial research. The preparation of ultrathin polydopamine (PDA) films with integrated protein pores containing phospholipids and an embedded domain of a membrane protein glycophorin A as simplified cell membrane mimics is reported. Large area, ultrathin PDA films are obtained by electropolymerization on gold surfaces with 10-18 nm thickness and dimensions of up to 2.5 cm 2 . The films are transferred from gold to various other substrates such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 57 publications
0
60
0
Order By: Relevance
“… 52 The mechanical properties of these films were investigated by micro-Brillouin light spectroscopy. 59 The authors reported a much higher Young’s modulus of ∼12 GPa, which allowed the easy transfer of the films.…”
Section: Resultsmentioning
confidence: 99%
“… 52 The mechanical properties of these films were investigated by micro-Brillouin light spectroscopy. 59 The authors reported a much higher Young’s modulus of ∼12 GPa, which allowed the easy transfer of the films.…”
Section: Resultsmentioning
confidence: 99%
“…Adding to this, PDA micropatterns further allow for site-specific immobilization of metal particles, chemical molecules, proteins, and cells, thus advancing applications, including but not limited to, biochips and biosensors. In this section, we summarize the repertoire of micro-/nanofabrication technologies for spatially controlled mussel-inspired patterning (Figure 12A), including photolithography, [27,46,100,[218][219][220] microcontact printing, [47,[221][222][223] inkjet printing, [48,224] electropolymerization, [225,226] microfluidics, [105,227] colloidal lithography, [228] and atomic force microscopy (AFM)-assisted lithography. [229]…”
Section: Spatially Controlled Polymerization: Patterning and Beyondmentioning
confidence: 99%
“…Reproduced with open access permission from ref. [ 226 ] . a–c) Schematic of the evaporation‐driven convective particle self‐assembly at the liquid contact line of printed pattern.…”
Section: Spatially Controlled Polymerization: Patterning and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16a,h,17 ] Furthermore, as a major advance in the field, we have demonstrated that off‐resonance and short pulse AFM‐IR (ORS‐nanoIR) can acquire infrared maps and spectra to determine protein secondary structure down to the single protein molecule level. [ 15,18 ] The ultimate spatial resolution of maps and spectra acquisition in contact mode is in the order of 10–20 nm. [ 15 ] Its scanning properties also allow it to analyze complex mixtures with co‐existing species such as amyloid, amorphous aggregates and pre‐fibrillar aggregates, which differ in secondary structure.…”
Section: Introductionmentioning
confidence: 99%